The Epistemic Modality in the Inaugural Speeches of Philippine Presidents - NGO, CRISTY GRACE; Cubelo , Ramil R. (CV. Tripe Konsultan, 2024)
This qualitative corpus-based study employing epistemic analysis uncovered the epistemic modality (EM) markers used and their communicative functions in the seven inaugural speeches of the seven Philippine 5th Republic presidents. The findings revealed the preponderant use of epistemic modal verbs with 152 occurrences (81.72%), followed by epistemic lexical verbs with 20 occurrences (10.75%), epistemic modal adverbs with 9 occurrences (4.84%), and epistemic modal adjectives with 5 occurrences (2.69%). Moreover, the top-five modal verbs operated in the presidential inaugurals are will with 97 instances (66.9%), can with 28 instances (19.31%), shall with 9 instances (6.21%), would with 6 instances (4.14%), and could with 5 instances (3.44%). Meanwhile, should and might were never used by any president. In this regard, the presidents are confident, committed, bold, and certain with their statements; some are tentative and quite confident but still communicatively sensitive and polite; and few are uncertain but still diplomatic. Further, the communicative functions of the EM markers were categorized to high-intermediate-low modality values, certain-probable-possible semantic meanings, and close-near-distant epistemic distances.